FAKTOR PERILAKU SEKS BEBAS PADA REMAJA - Yesi Septina Wati (LPPM Universitas Muhammadiyah Riau, 2017)
Unhealthy sexual behavior among teenagers, especially teenagers who are not married tend to increase. WHO data as much as 6 % of respondents reported having had sexual intercourse before marriage. This is evident from several studies that show that the teenage years when he first entered active sexual relationship varies between the ages of 14-23 years of age and most were between 17-19 years old. The purpose of this study was to determine the relationship between gender, age, staying with whom, facilities, media, peers, school, of environment, knowledge of sex behavior in adolescents. This type of research is a kind of cross-sectional approach. The population of this study were all high school students in Jakarta district Lenteng Negri 38 grand for 820 people. The research sample is taken into a purposive sampling of 90 students. The results showed that there is a relationship between variables, namely gender variable (p value = 0.030 < 0.05), the variable age ( p value = 0.003 < 0.05), the variable media (p value = 0.026 < 0.05), the variable communication peers ( p value = 0.035 < 0. 05 ), school environment variables (p value = 0.037 < 0.05 ), the variable knowledge ( p value = 0.041 < 0.05 ). The results obtained from the study of sex behavior in adolescents in Negri SMA 38 Jakarta South Jakarta district has bad manners and good knowledge, it is recommended that schools need to supervise students on media and requires further research on cultural factors.